FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BERPRESTASI PADA HIMPUNAN MAHASISWA ISLAM (HMI) UNIVERSITAS PALANGKA RAYA PERIODE 2025/2026 - Febriani Amanda; Nofi Mustikasari; Keren Monika; Dewi Virna Sipayung; Oktavia Ramadhani; Nur Hidayah Mafiroh; Timoti Elwisto Sipayung; Siti sariyah; Elsa Natalia Girsang; Tri Wulandari; Clementina Ayudhea; Romiaty Romiaty; Susi Sukarningsi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors influencing Achievement Motivation among members of the Islamic Students Association (HMI) at the University of Palangka Raya for the 2025/2026 period. Achievement motivation is viewed as a fundamental drive for students in achieving personal and professional success. HMI, as a cadre-based and learning organization, plays a crucial role in shaping leaders with integrity (Good Governance) and a strong sense of responsibility to realize a just and prosperous society in harmony with Islamic and Indonesian values.This study adopts a quantitative approach using a population survey method. Data were collected through questionnaires based on the Likert Scale from all HMI members at the University of Palangka Raya, class of 2025/2026. Descriptive analysis results show that the overall Achievement Motivation of HMI members at the University of Palangka Raya falls into the high category.This strong level of motivation is reflected in the high level of agreement across six measured factors. The factor with the highest percentage is Risk Consideration (94% strongly agree and agree), indicating mature thinking in selecting challenging tasks. Other strong factors include high awareness of Task Completion Time (85.6%) and Responsibility (75%). On the other hand, the Feedback Awareness factor shows the lowest percentage of agreement (65.3%) compared to other factors.